Implikasi Willow Project Terhadap Perubahan Iklim Dan Ekosistem Menurut Hukum Lingkungan Internasional - Ferry, Jasmine Syifa Rahmadilla; H.Z, Evi Deliana; Diana, Ledy (Peneliti.net, 2025)
Climate change is one of the main issues in international environmental law that continues to receive global attention. One of the projects in the spotlight is the Willow Project, a fossil fuel exploitation project in the Arctic region that has sparked international controversy. This project is considered to have minimally conducted adequate environmental studies and shows an imbalance between economic interests and environmental protection, thus raising concerns from various parties in the international community. This research uses a normative method with a literature study approach to examine the principles contained in various international environmental law instruments. The research results show that the Willow Project presents major challenges in international environmental law, especially related to climate change mitigation obligations as regulated in the Paris Agreement, biodiversity conservation in the Convention on Biological Diversity (CBD), as well as the principles in the UNFCCC, UNDRIP, UDHR, Rio Declaration, and Stockholm Declaration. In addition, this project also reflects the United States' inconsistency in strengthening international partnerships. The research results show that the Willow Project presents a major challenge to the implementation of international environmental law. Carbon emissions generated during the project's operational period contribute significantly to global climate change, such as melting polar ice and rising sea levels. In addition, the ecological impacts of noise and light pollution also disrupt the life patterns of wildlife, especially endangered species such as polar bears. In addition to impacting the natural environment, the project also poses serious risks to the health of local communities and their right to live in a clean and healthy environment. Therefore, a review of similar projects is needed and stronger enforcement of environmental commitments in international forums.